Analisis Ekoteologi dalam Buku Nyanyian Kidung Keesaan dalam Sudut Pandang Dokumen Keesaan Gereja Persekutuan Gereja-gereja di Indonesia - Elia, Natanael Budiman (STFT Jakarta, Indonesia, 2025)
This study explores the role of hymns in Kidung Keesaan as a medium for conveying ecological theology within the context of Indonesian churches. The analysis of hymn lyrics reveals that key principles of ecotheology, such as the recognition of nature as God's creation, harmony within creation, and God's continuous sustenance, are clearly reflected. These hymns encourage congregations to care for and preserve the environment as an act of faith. However, there is room for further development in aligning ecotheological messages with practical actions in congregational life. The study recommends a more applied approach in utilizing church hymns as educational tools and promoting ecological action among congregations.